Optimization of Groundwater Well Discharge Capacity Using Step Drawdown Test Post-Earthquake in Biromaru, Sigi District, Central Sulawesi - Hamad, Harly; Aswadi, Muhammad; Lapalani, Cindy Ziqni Noviar (Jambura Geoscience Review, 2025)
The effectiveness of groundwater wells in tectonically active regions remains insufficiently understood due to the lack of integrative hydrogeological evaluations. This study aims to characterize the hydraulic performance of five groundwater wells in Biromaru District, Sigi Regency, an area affected by the 2018 Central Sulawesi earthquake. A combination of the Neuman method and the Hantush-Bierschenk approach was employed to evaluate key aquifer parameters, including transmissivity, storativity, specific yield, and well loss coefficients. Step drawdown tests and time-drawdown data were analyzed to determine aquifer responses under controlled pumping conditions. The results show a clear variation in transmissivity and storativity among wells, indicating heterogeneous subsurface characteristics possibly influenced by post-seismic compaction. Wells 1 and 3 demonstrated high transmissivity and efficiency, supported by C values below 0.5, signifying well integrity and optimal construction. Conversely, well 2 exhibited low hydraulic performance, suggesting lithological constraints or structural deficiencies. The combination of analytical methods provided a robust framework for interpreting aquifer-well interactions in a post-disturbance setting. This study contributes to a deeper understanding of groundwater behavior in seismically disturbed regions and emphasizes the importance of incorporating multi-method approaches in hydrogeological assessments. The findings can serve as a reference for groundwater resource planning, well rehabilitation, and adaptive water management in vulnerable areas like Sigi Regency.